Integrasi Akuntansi Lingkungan Untuk Kinerja Bisnis Dan Pertanggungjawaban Yang Komprehensif - Dinda Indri L. L.; Intan Sari; Riski Ilham Syah Saputra; Sonya Widia Sari; Rika Damai Yanti; Ersi Sisdianto (Pusat Riset dan Inovasi Nasional, 2024)
Abstract. Growing awareness of environmental issues has encouraged companies to consider environmental impacts in their operations. The integration of environmental accounting becomes a key focus for measuring, reporting and managing these impacts, creating better engagement in sustainable practices. This article aims to investigate the benefits of environmental accounting integration in the context of comprehensive business performance and accountability. We seek to identify direct links between this integration and business performance, as well as explore its impact on corporate accountability for environmental impacts. This research uses a literature study approach by conducting a comprehensive literature review to collect information from various academic and practical sources. Literature analysis was conducted to summarize key findings and identify trends and knowledge gaps. The integration of environmental accounting has a positive impact in increasing operational efficiency, supporting sustainable innovation, and strengthening the company's image through accountability and transparency. Strategic decisions based on environmental accounting information can increase engagement in sustainable business practices and ensure compliance with regulations.